Plant polysaccharides in the regulation of the tumor microenvironment: a review - Yuhua Li; Yang Sun; Gui’e Chen; Xinrong Yuan; De Cai (Carbohydrate Polymer Technologies and Applications, 2025)
As natural bioactive macromolecules, plant polysaccharides exhibit significant potential in tumor therapy through the regulation of the tumor microenvironment (TME). This review systematically synthesizes 88 studies retrieved from PubMed and CNKI databases (2015–2025), demonstrating that plant polysaccharides modulate the TME via multiple-target mechanisms: polarizing tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs), inhibiting vascular endothelial growth factor (VEGF)-mediated angiogenesis, and remodeling the extracellular matrix (ECM). Such regulatory effects reverse immunosuppression, disrupt the nutrient supply to tumors, and hinder metastasis, thereby providing novel strategies for combined cancer therapy. Notably, this review uniquely offers a systematic integration of immunological, metabolic, and structural regulatory perspectives to comprehensively address the complexity of the tumor microenvironment (TME), setting it apart from prior studies that predominantly focused on isolated mechanisms. It emphasizes how structural heterogeneity—such as variations in glycosidic bond types and molecular weight—influences bioactivity, and identifies key translational challenges, including the standardization of extraction methods and the development of nanodelivery systems. To address these limitations, future research should emphasize interdisciplinary collaboration, particularly in the fields of nanotechnology and chemical synthesis, and explore synergistic applications with immunotherapies. Such efforts are critical for advancing plant polysaccharides from preclinical investigations toward clinical implementation.